Methanolic extract of Mitragyna speciosa Korth leaf inhibits ethanol seeking behaviour in mice: involvement of antidopaminergic mechanism - Vijeepallam, Kamini; Pandy, Vijayapandi; Murugan, Dharmani Devi; Naidu, Murali (Springer, 2019)
In the current study, the effect of methanolic extract of Mitragyna speciosa leaf (MMS) against the rewarding and reinforcing properties of ethanol using a mouse model of conditioned place preference (CPP) and runway model of drug self-administration was studied. Subsequently, the effect of MMS on dopamine level in the nucleus accumbens (NAc) of the mouse brain was further investigated. From the data obtained, MMS (50 and 75 mg/kg, p.o.) significantly reversed the ethanol-place preference in mice, which is similar to the effect observed in the reference drugs acamprosate (300 mg/kg, p.o.) and clozapine (1 mg/kg, p.o.) treatment groups in CPP test. Likewise, the escalating doses of ethanol-conditioned mice reduced the runtime to reach goal box, infers the positive reinforcing effects of alcohol. Interestingly, MMS (50, 75 and 100 mg/kg, p.o.) significantly prolonged the runtime in ethanol-conditioned mice. Besides, MMS (50 and 75 mg/kg, p.o.) and reference drugs; acamprosate (300 mg/kg, p.o.) and clozapine (1 mg/kg, p.o.) treated mice significantly decreased the alcohol-induced elevated dopamine level in the NAc region of the brain. Overall, this study provides first evidence that MMS inhibits ethanol seeking behaviour in mice. Based on these findings, we suggest that Mitragyna speciosa may well be utilized for novel drug development to combat alcohol dependence. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.